A Paradox of Plenty: Renewable Energy on Navajo Nation Lands. Issue 8 (2nd August 2016) - Pasqualetti, Martin J.; Jones, Thomas E.; Necefer, Len; Scott, Christopher A.; Colombi, Benedict J.
ABSTRACT: A persistent paradox in the global boom of renewable energy revolves around how little of its vast potential has been developed on Native American lands. For economic and environmental reasons, attempts to reverse this pattern are on the rise. Such plans will encounter many unique conditions, particularly those related to tribal norms, customs, and histories. This article examines the prospect of renewable energy (RE) development on the Navajo Nation of the American Southwest. We examine its potential in light of past energy projects, current jurisdictions and control, and the cultural and social heritage of the Navajo Nation. We find that robust RE development on Navajo Nation lands will remain hindered without accounting for Navajo values, intratribal and tribal–nontribal politics, and their relationship to a multifaceted set of regulatory procedures. Without due consideration of these factors, RE development on Navajo and other Native American lands will continue to be slow and disappointing.